2013
DOI: 10.1007/s10548-013-0294-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiphasic 40 Hz Oscillatory Current Stimulation Affects Bistable Motion Perception

Abstract: When viewing ambiguous stimuli, conscious perception alternates spontaneously between competing interpretations of physically unchanged stimulus information. As one possible neural mechanism underlying the perceptual switches, it has been suggested that neurons dynamically change their pattern of synchronized oscillatory activity in the gamma band (30-80 Hz). In support of this hypothesis, there is correlative evidence from human electroencephalographic (EEG) studies for gamma band modulations during ambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
180
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 64 publications
14
180
1
Order By: Relevance
“…Previous studies have found large similarities for theta activity during the perception of ambiguous and unambiguous figures (Ehm, et al, 2011;Nakatani & van Leeuwen, 2005;Strüber, et al, 2014), but differences of theta activity indicating increased top-down requirements for the perception of ambiguous in comparison to unambiguous figures have also been found . In this study, we did not directly compare the ambiguous and unambiguous task, because the switching rates differed between both tasks, which seem to be a requirement for comparability (Nakatani & van Leeuwen, 2005;Strüber, et al, 2000;Strüber, et al, 2001).…”
Section: Limitations Of the Studymentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have found large similarities for theta activity during the perception of ambiguous and unambiguous figures (Ehm, et al, 2011;Nakatani & van Leeuwen, 2005;Strüber, et al, 2014), but differences of theta activity indicating increased top-down requirements for the perception of ambiguous in comparison to unambiguous figures have also been found . In this study, we did not directly compare the ambiguous and unambiguous task, because the switching rates differed between both tasks, which seem to be a requirement for comparability (Nakatani & van Leeuwen, 2005;Strüber, et al, 2000;Strüber, et al, 2001).…”
Section: Limitations Of the Studymentioning
confidence: 90%
“…A more explicit way to reveal top-down influences on multistable perception was undertaken by investigating voluntary slowing and accelerating of the individual reversal rate (Strüber & Stadler, 1999), which modulated the reversal-related delta and gamma activity (Mathes, et al, 2006). A functional role for interhemispheric gamma-band coherence over parieto-occipital areas in bistable motion perception was recently demonstrated using transcranial alternating current stimulation (tACS, Helfrich et al, 2014;Strüber, Rach, Trautmann-Lengsfeld, Engel, & Herrmann, 2014). An increase of posterior beta amplitudes after the onset of an ambiguous stimulus occurred after a perceptual change (Yokota, Minami, Naruse, & Nakauchi, 2014), its suppression has been related to top-down mechanisms stabilizing a new percept (Kloosterman et al, 2014).…”
Section: Future Prospects: Disturbances Of the Interplay Between Diffmentioning
confidence: 99%
“…TACS has also been applied in the gamma frequency band in order to modulate perception of bistable motion (Strüber et al, 2014). It had previously been shown that this type of motion perception depends on changes of the interhemispheric coherence in this frequency band.…”
Section: Combined Behavioral and Electrophysiological Effects (Offlinmentioning
confidence: 99%
“…The local synchronization will be reflected in an amplitude increase of intracortically measured local field potentials or scalp EEG, while long-range synchronization would show up as an increase in oscillatory phase coupling between signals in two areas. Indeed, multiple studies point to the importance of a transient increase in gamma band power and coherence for global perception of hierarchical stimuli as well as for interhemispheric integration and illusory contour perception (Rose and Büchel, 2005;Rose et al, 2006;Strüber et al, 2013;Tallon-Baudry et al, 1996). In addition, there is accumulating evidence for the role of theta and beta phase synchrony in grouping and illusion perception, which may be mediating information exchange between higher and lower level areas (Hanslmayr et al, 2013;Hipp et al, 2011;Keil et al, 2014;Romei et al, 2011;Smith et al, 2006;Volberg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%